2019
DOI: 10.1080/14767058.2019.1651283
|View full text |Cite
|
Sign up to set email alerts
|

Structured clinical examinations in labor: rekindling the craft of obstetrics

Abstract: Objectives: Exact knowledge of fetal station and position is of paramount importance for reliable surveillance of labor progress and a prerequisite for safe operative vaginal procedures. Detailed clinical assessments are thoroughly described in old textbooks, but almost forgotten in contemporary obstetrics. Ultrasound is suggested as an objective diagnostic tool in active labor. Several publications have demonstrated a low correlation between ultrasound and clinical assessment of fetal head station and positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…33 We observed that the fetal head position could only be correctly identified in a minority of cases at inclusion, but even at the last examination, only around two-thirds of the clinical staff felt they could determine the position but with increasing accuracy. This is very much in agreement with other studies, 6e8,34,35 but Iversen et al 4 have shown that this can be improved with structured clinical assessment.…”
Section: Clinical Significancesupporting
confidence: 92%
See 1 more Smart Citation
“…33 We observed that the fetal head position could only be correctly identified in a minority of cases at inclusion, but even at the last examination, only around two-thirds of the clinical staff felt they could determine the position but with increasing accuracy. This is very much in agreement with other studies, 6e8,34,35 but Iversen et al 4 have shown that this can be improved with structured clinical assessment.…”
Section: Clinical Significancesupporting
confidence: 92%
“…Occiput posterior (OP) and transverse positions have been associated with poorer outcomes of labor for both the mother and fetus. 1e3 At present, position is predominantly assessed clinically, and although some obstetricians become skilled at this examination, 4,5 many operators never acquire it fully. The use of ultrasound has been shown to be more accurate in determining fetal head position 6e11 and has a shorter learning curve than clinical examinations, 12 and the introduction of this skill has been encouraged.…”
Section: Introductionmentioning
confidence: 99%
“…12 A revival of digital examination with sustainable technologic strategies to improve its objectivity may therefore be an optimal development both for training purposes and possibly for future clinical use in labor wards. 13 Our study demonstrates that the use of a sensorized platform- use of the NAV system while conducting a gynecologic examination and, in turn, to evaluate the usefulness of introducing such a system to the training program of medical students. Future studies will be conducted by organizing the operators into two groups, one using the SIM and one using the NAV system, to evaluate the difference between the learning curves of the two groups.…”
Section: Achieving a Correct Diagnosis Of Labor Progression With Vagi-mentioning
confidence: 80%
“…Although the abandonment of basic obstetrical skills in favor of more technologic approaches is unrealistic for a number of economical and logistical reasons, it would also carry a loss of the basic “know‐how” for following generations 12 . A revival of digital examination with sustainable technologic strategies to improve its objectivity may therefore be an optimal development both for training purposes and possibly for future clinical use in labor wards 13 …”
Section: Discussionmentioning
confidence: 99%
“…The cardinal movements mostly occur during the second stage of labor and accordingly disproportion or resistance of the maternal pelvic cavity and the fetus becomes apparent [15]. In general, the vertex or cephalic presentation of fetuses enter the pelvis with the sagittal suture lying in the transverse diameter of pelvis [16]. When fetal head engages into the pelvic cavity, occiput usually comes in the left side, resulting in the right parietal bone exposed to the anterior pelvic bones, which are narrower than the posterior structures [17,18].…”
Section: Discussionmentioning
confidence: 99%